L’immaginario ontologico della macchina per dipingere: Alfred Jarry, On Kawara, Nam June Paik, Michael Snow, Anish Kapoor - Chopplet, Marc (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2023)
This article is an investigation. Alfred Jarry, poet and writer, proposes at the end of the 19th century the apocalyptic representation of a creative machine in a ruined Paris. But this vision is still partly ours. The being of this painting machine is in question. Is it a mechanic gone mad, a beast, a dehumanized double or on the contrary revealed, a demiurge? And where do these questions come from? Which scientific and technological ontological imaginary is invested there? What place does it occupy in the work of contemporary artists?